Electrochemical, Electrocatalytic Dioxygen Reducing and Dielectric Relaxation Properties of Non-Peripheral Tetra-2,3-dihydro-1H-inden-5-yloxy Substituted Phthalocyanines - ÖZKAYA, ALİ RIZA; ORMAN, EFE BATURHAN; ALTUN, SELÇUK; ODABAŞ, ZAFER (ELECTROCHEMICAL SOC INC, 2015)
Novel metal-free and metallophthalocyanines were synthesized by cyclotetramerization of 3-(2,3-dihydro-1H-inden-5-yloxy)phthalonitrile and characterized. The redox properties of these compounds were investigated by cyclic voltammetry, square-wave voltammetry, controlled-potential coulometry and in situ spectroelectrochemistry in dimethylsulfoxide and dichloromethane. The compounds displayed metal and/or phthalocyanine ring-based reduction and oxidation processes. The color changes associated with these redox processes and electrogenerated anionic and cationic redox species were recorded with in situ electrocolorimetric measurements. The electrocatalytic performances of the compounds toward oxygen reduction reaction having vital importance for fuel cell applications were determined by hydrodynamic rotating disk and bipotentiostatic rotating ring-disk voltammetry measurements. The Vulcan XC-72/Nf/FePc modified glassy carbon electrode showed much higher catalytic performance toward oxygen reduction than those of the other modified ones. Furthermore, the field dependence of dielectric response and the conductivity of the samples were measured as a function of frequency and temperature. Dielectric relaxation behaviors of the phthalocyanines were also investigated. The ITO/ZnPc/Au sample showed the highest value of epsilon'(omega) as compared to the other samples. The analysis of the real and imaginary parts of the dielectric permittivity with frequency was carried out assuming a distribution of relaxation times as well as the scaling behavior of the dielectric loss spectra. (C) 2015 The Electrochemical Society. All rights reserved.
Keywords: OXYGEN REDUCTION REACTION; METAL-FREE; SPECTROELECTROCHEMICAL PROPERTIES; TITANYL PHTHALOCYANINES; COPPER PHTHALOCYANINE; SOLAR-CELLS; COMPLEXES; CATALYSTS; METALLOPHTHALOCYANINES; MANGANESE